Secondary metabolites from Raphanus sativus - Ragasa, Consolacion Y. (Animo Repository, 2015)
Chemical investigation of the dichloromethane extract of the freeze-dried roots of Raphanus sativus led to the isolation of β-sitosteryl-3β-glucopyranoside-6'-O-palmitate (1), α-(7Z,10Z,13Z)-hexadecatrienoic acidmonoglyceride (2), β-sitosterol (3), triacylglycerols (4), α-linolenic acid (5a), and linoleic acid (5b). The structures of 1-5b were identified by comparison of their NMR data with literature data.